2012
DOI: 10.1111/j.1476-4431.2012.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonoclot evaluation of whole blood coagulation in healthy adult dogs

Abstract: Sonoclot provides viscoelastic evaluation of canine whole blood coagulation and correlated to several TEG parameters and fibrinogen. A standard protocol and reference intervals were established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…ACT and CR values were obtained at every time point for all dogs, although timing necessitated the termination of some runs before the PF could be calculated. Baseline ACT and CR fell within the institutional reference interval (ACT 56.0–154.0 seconds, CR 14.9–46.0) at hour 0 on day 1 except for 1 dog with a slightly steeper clot rate (52). The final sample for all dogs on day 4 also fell within the institutional reference interval.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…ACT and CR values were obtained at every time point for all dogs, although timing necessitated the termination of some runs before the PF could be calculated. Baseline ACT and CR fell within the institutional reference interval (ACT 56.0–154.0 seconds, CR 14.9–46.0) at hour 0 on day 1 except for 1 dog with a slightly steeper clot rate (52). The final sample for all dogs on day 4 also fell within the institutional reference interval.…”
Section: Resultsmentioning
confidence: 88%
“…The Sonoclot analyzer provides information on the entire hemostasis process in both a qualitative graph (Sonoclot Signature) and as quantitative results: the activated clotting time (ACT), the clot rate (CR), and the platelet function (PF) . Reference intervals for the sonoclot parameters in healthy adult dogs are available …”
mentioning
confidence: 99%
“…17 Briefly, 20 µL of 0.2M CaCl 2 j was added to each cuvette, and the solution was warmed to 37°C. 17 Briefly, 20 µL of 0.2M CaCl 2 j was added to each cuvette, and the solution was warmed to 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Using such a complex scoring system, groups with low (15%) and high mortality (40%) have been discriminated [20]. Previous studies have suggested that a combination of the APACHE II and ISTH scores predict mortality in critically ill patients better than the APACHE II score alone [21].…”
Section: Discussionmentioning
confidence: 99%
“…4 mg/l, respectively [6]. The diagnostic values for ACT (119-195 s), clot rate (7-23 sig/min), and platelet function (!1.5) were therefore chosen as discriminating values to separate patients with normal and pathological Sonoclot findings [10,20]. All laboratory tests to confirm or reject the diagnosis of overt DIC were consecutively measured when DIC was clinically suspected on the basis of the symptoms of the patient or on laboratory data.…”
Section: Definitions and Treatmentmentioning
confidence: 99%